1998
DOI: 10.1086/515297
|View full text |Cite
|
Sign up to set email alerts
|

Immunologic Determinants of Disease Evolution in Localized Cutaneous Leishmaniasis due toLeishmania major

Abstract: Localized cutaneous leishmaniasis caused by Leishmania major is polymorphic in its clinical presentation and evolution. Clinical and parasitologic features and disease evolution of 112 Tunisian patients was evaluated. The expression of interleukin (IL)-4, IL-6, IL-10, IL-12 (p40), interferon (IFN)-gamma, and tumor necrosis factor (TNF)-alpha mRNA was analyzed by reverse transcription-polymerase chain reaction in 73 biopsies. Cytokine mRNA expression varied individually over a wide range; TNF-alpha, IL-6, and I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
84
0
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(98 citation statements)
references
References 37 publications
12
84
0
2
Order By: Relevance
“…In relation to other cytokines, such as IL-2, they have been demonstrated in vitro and in situ, with a low expression. Additionally, the immune response of the Old World LCL caused by L. major, L. tropica and L. aethiopica, is characterized by this same cytokine profile (Th1), also observed by many investigators 19,29 . However, in acute and chronic lesions of LCL, studied in situ and with stimulation of peripheral blood mononuclear cells by Leishmania antigen, the cytokines in acute lesions show a tendency to the Th1 type, whereas, in chronic lesions, there is a tendency to a mixed cytokine type 19,29 .…”
Section: Discussionsupporting
confidence: 68%
“…In relation to other cytokines, such as IL-2, they have been demonstrated in vitro and in situ, with a low expression. Additionally, the immune response of the Old World LCL caused by L. major, L. tropica and L. aethiopica, is characterized by this same cytokine profile (Th1), also observed by many investigators 19,29 . However, in acute and chronic lesions of LCL, studied in situ and with stimulation of peripheral blood mononuclear cells by Leishmania antigen, the cytokines in acute lesions show a tendency to the Th1 type, whereas, in chronic lesions, there is a tendency to a mixed cytokine type 19,29 .…”
Section: Discussionsupporting
confidence: 68%
“…All these studies demonstrate the variability of the clinical presentation of LCL caused by L. (L.) mexicana regarding the number, form, size, and location of lesions as it has been described in other species of Leishmania (Louzir et al 1998). Various hypotheses have been proposed to explain such variability: (a) differences in parasite´s virulence; (b) differences in skin permeability; (c) individual variation in the host´s genetic susceptibility; (d) individual human differences of attraction for phlebotomine sand flies (Llanos-Cuentas & Campos 1988).…”
Section: Discussionmentioning
confidence: 53%
“…The skin permeability hypothesis to the sand fly bite was evaluated by Esterre et al (1987), however, they did not show convincingly that the differences between the patients and controls were significant. Louzir et al (1998) studying the immunologic determinants of disease evolution in LCL due to L. major, found that an unfavorable clinical outcome was not related to an inadequate Th1 cell response, and suggested that the macrophage-activating effect of IFN-γ may be inhibited by the concomitant expression of IL-10. Finally, McHugh et al (1996) pointed out that although the Leishmania parasites infesting humans in Texas share a high genetical similarity with L. (L.) mexicana isolates from southeast Mexico, the epidemiology and ecology of the disease in Texas and Mexico are different.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, the severity of visceral leishmaniasis has been most closely associated with increased levels of IL-10 (24, 21). IL-10 production is also correlated with lesion progression in patients with cutaneous leishmaniasis (25). A Splenocytes from BALB/c IL-10 Ϫ/Ϫ and wild-type mice were stimulated in vitro in the presence of freeze-thawed Ag (5 ϫ 10 6 parasites Eq/ml) and cell supernatants were harvested at 72 h and assayed for IFN-␥ and NO 2 .…”
Section: Discussionmentioning
confidence: 99%